A Novel Whole Gene Deletion of BCKDHB by Alu-Mediated Non-allelic Recombination in a Chinese Patient With Maple Syrup Urine Disease - Liu, Gang; Ma, Dingyuan; Hu, Ping; Wang, Wen; Luo, Chunyu; Wang, Yan; Sun, Yun; Zhang, Jingjing; Jiang, Tao; Xu, Zhengfeng (Frontiers in Genetics, 2018)
Maple syrup urine disease (MSUD) is an autosomal recessive inherited metabolic disorder caused by mutations in the BCKDHA, BCKDHB, DBT, and DLD genes. Among the wide range of disease-causing mutations in BCKDHB, only one large deletion has been associated with MSUD. Compound heterozygous mutations in BCKDHB were identified in a Chinese patient with typical MSUD using next-generation sequencing, quantitative PCR, and array comparative genomic hybridization. One allele presented a missense mutation (c.391G>A), while the other allele had a large deletion; both were inherited from the patient’s unaffected parents. The deletion breakpoints were characterized using long-range PCR and sequencing. A novel 383,556 bp deletion (chr6: g.80811266_81194921del) was determined, which encompassed the entire BCKDHB gene. The junction site of the deletion was localized within a homologous sequence in two AluYa5 elements. Hence, Alu-mediated non-allelic homologous recombination is speculated as the mutational event underlying the large deletion. In summary, this study reports a recombination mechanism in the BCKDHB gene causing a whole gene deletion in a newborn with MSUD.